Cross-Cutting Themes in Major Article IV Consultations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper is part of a broader on-going effort to bring a more cross-country perspective to bilateral surveillance, taking advantage of a cluster of Article IV consultations with five systemically important economies concluded in July. With the five economies-the United States, the Euro area, China, Japan, and the United Kingdom-accounting for two-thirds of global output and three quarters of capital flows, the nature of linkages and consistency of policy responses across the systemic five (S5) has important implications for the world economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States